Microstructural characterisation of biocompatible sol-gel derived vanadium doped TiO2 on Ti substrates - Marlafeka, S.; Allison, F.; Grant, D.M.; Harrison, P.G.; Brown, Paul D. (IOP Publishing Ltd, 2001)
Sol-gel derived pure titania is compared with vanadium and / or aluminium modified titania deposited by spin coating on pure titanium substrates annealed at 300C and 650C. Reflection high-energy electron diffraction indicated the presence of anatase from the surface layers of samples annealed at 300C with a transition to rutile with increasing annealing temperature and addition of vanadium. Cross-sectional transmission electron microscopy indicated a gradation of Ti-O phases through the layer with the dominant presence of rutile. Aluminium was found to inhibit grain growth while vanadium promoted crystallisation.